Reasons for quitting the smoking cessation in people - Kayacık, İbrahim; Aydın Berktaş, Özlem; Duysak, Lale; Bayır, Yasin (Journal of Dependence, 2017)
Objective: Our aim in this study is to guide the new work to be done to those who want to quit smoking, to give the points to be given priority and to give up smoking cessation in this frame by questionnaire about reasons of smoking cessation.Material and Methods: Administrative staff and academicians in Atatürk University who left the cigarette were applied a face to face questionnaire. The data of 128 participants in the survey were included in the study. The distribution of drop outs according to demographic groups was examined.Results: Age at onset of cigarette smoking was between 0-18% in 44%, 18-25% in 52% and 25% in 4%. It was determined that 67.2% of those who quit smoking had a fear of deterioration of health, 59.7% of them increased their quality of life, and 46.9% of them were affected by illness such as bad smell of cigarette. It was determined that television ads were effective at 1,6% and 0,8% of smoking cigarettes.Conclusion: In the first stage of smoking cessation, Although it is fearful that cigarette will harm health, it is determined that it is one of the important factors that one wants to quit smoking. In future cigarette quit campaigns, it is thought that the efforts to increase cigarette smoking behavior according to the demographic characteristics of the cigarette smokers and to reach an adequate awareness of the health risks of cigarettes in general smoking cessation campaigns should be continued and the ways to encourage smoking cessation should be increased.
Keywords: Survey; Smoking Cessation; Cigarette